Influence of digital literacy in classroom and attitudes on inclusive digital literacy pedagogy of in-service teachers in Malaysia / Wu Miaomiao - Wu , Miaomiao (2024)
The convergence of digitization and inclusive education in IR 4.0 has instigated alterations in educational content and teaching methods, necessitating educators to possess digital literacy and adapt to novel pedagogical approaches, especially for primary school teachers at the basic education level. Despite Malaysia’ s active involvement in technological advancements and enhancements in inclusive education, the outcomes have proven unsatisfactory. Therefore, this study identified the impact of digital literacy on in-service teachers in inclusive classrooms and their attitudes toward their inclusive digital literacy pedagogy in Malaysian primary schools during the IR 4.0 era. The study used cluster sampling and simple random sampling techniques to recruit participants from Kuala Lumpur and Selangor, Malaysia. This study designed instruments to measure teachers’ digital literacy, attitude, and inclusive digital literacy pedagogy in inclusive classrooms. Reliability values for all three instruments were above 0.9, factor loadings for each item were above 0.7, and model indices and discriminant validity values were acceptable. The results indicated that the reliability and validity of these instruments were satisfactory and can be used to assess the level of teachers accordingly. The results of the assessment also revealed that teachers had a positive attitude toward incorporating technology in inclusive classroom, possessed some knowledge of inclusive digital literacy pedagogy, but there were shortcomings in action. Moreover, teachers’ digital literacy proficiency was moderate, particularly in areas such as digital content creation and problem-solving skills, which remained relatively underdeveloped. Regarding the model’ s design, PLS analysis was used to assess and establish the model. Findings showed that teachers’ digital literacy in the classroom has a significant impact on inclusive digital literacy pedagogy (β= 0.789, T=27.895, P =0.000); teachers’ digital literacy in the classroom were positively related to attitude (β= 0.776, T=26.991, P=0.000); teachers’ attitude have a direct impact on their inclusive digital literacy pedagogy (β= 0.754, T=24. 188, P=0.000); and attitude played a partially mediating role in the impact of teachers’ digital literacy in inclusive classrooms on their inclusive digital literacy pedagogy. From the above, it can be concluded that in IR 4.0, primary school teachers in inclusive education in Malaysia also need to improve their digital literacy, continue to maintain and even enhance their positive attitude towards integrating technology in an inclusive classroom, and endeavor to know and do inclusive digital literacy pedagogy. An important way to realize this vision is to emphasize and develop the professional development of teachers. This study bridges the research gap on digital literacy in the classroom and inclusive digital literacy pedagogy, which is innovative and academically valuable. Simultaneously, this study also provides some references for in-service teachers’ future training. However, due to objective constraints, this study has a limited study area and sample in Malaysia. Future endeavors will focus on expanding and deepening research in this domain.